Improving the Quality of Tempe Products with GMP and Model Based Integrated Process Improvement In SME’s Pacarkeling - Wahid, Abdul (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
Small and Medium Enterprises, Tempe Pacarkeling is one of the centers for Small and Medium Enterprises in Pasuruan. This Small and Medium Enterprise Center is located in Pacarkeling-Kejayan-Pasuruan Village. One of the UKM that was used as the research object was the Tempe UKM owned by Mr. Muizzi. In the production process, there is still less attention to environmental cleanliness. So it requires an assessment of Good Manufacturing Practice (GMP) as an assessment of the environment and working conditions. In addition, this study aims to evaluate the level of application of GMP. Based on the research conducted, the results of the evaluation of the application of GMP as a whole, the total value of GMP application of all respondents obtained 8,145 points or an average of 247 points, while the percentage of the deviation value is 46% and the conformity value is 54% in the aspects of Good Manufacturing Practice (GMP) so that it has not meet the GMP criteria. Evaluation obtained from processing GMP data, the level of seriousness in implementing Good Manufacturing Practice (GMP) in this UKM is 247 points, which means that it is at the classification level ((nx2) +1) to (nx3), which is very good.